A new indole-type alkaloid from the roots of Clematis florida var. plena. Issue 20 (18th October 2019) - Sun, Kai-Hui; Ma, Xin-Hua; Zeng, Xian-Ming; Lin, Zhong-Yue; Cai, Yu-Mei; Zhang, Hai-Tao; Lin, Xiao-Yan; Feng, Shi-Biao; Zhong, Tian-Hua; Zhang, Yong-Hong
Abstract: One new indole-type alkaloid, α -L-rhamnopyranosyl-(1→6)- β -D- glucopyranosyl 6-methoxy-3-indolecarbonate (1 ), together with three known alkaloids (2 –4 ), one aromatic acid (5 ) and five known saponins (6 –10 ), was isolated from the roots of Clematis florida var. plena . Their structures were established by NMR spectroscopic analysis and acid hydrolysis. In in vivo anti-inflammatory activity, n -butanol extract was found to be potent against ear edema in mice, with inhibition rate of 48.7% at a dose of 800 mg/kg. Furthermore, compounds8 and9 obtained from the n -butanol extract exhibited significant anti-inflammatory activities with inhibition rates of 50.9% and 54.7% at a dose of 200 mg/kg. Graphical Abstract: